2016
DOI: 10.30818/jpkm.2016.2010204
|View full text |Cite
|
Sign up to set email alerts
|

Use of Information Technology among Performers Micro Small Medium Enterprises in the Border Area (Study in Belu, East Nusa Tenggara) (Penggunaan Teknologi Informasi di Kalangan Pelaku Usaha Mikro Kecil Menengah di Daerah Perbatasan (Studi di Kabupaten Belu Provinsi Nusa Tenggara Timur))

Abstract: Conditions in the communities along the border are generally poor with a low level of welfare and living in isolated areas. One effort to improve the economy of the border area communities is through the empowerment of micro, small, and medium enterprises (SMEs). The presence of information technology (IT) to change the way in the business by providing new opportunities and challenges for the development of SMEs. The purpose of this study was to describe the use of IT in the development of SMEs. The method use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
1
0
8
Order By: Relevance
“…Research related to the role of Islamic banks in the strengthening of SMEs also have a lot to do, citing the results of the analysis of the Ministry of Commerce that SMEs have a very important role in the economic growth of a country. Saleh & Hadiyat (2016), it is in line with the results of the study (Rini, 2017), (Prayogi & Siregar, 2017), (Kara, 2014), (Cheng & Degryse, 2010) in his research revealed that poor communities in border areas are able to improve their standard of living by empowering MSMEs, but are still constrained by the level of education in managing MSMEs. (Trimulato, 2017), (Aurora Lubis, 2016), (Darwanto, 2013) in his research identified that the most suitable Islamic banking financing for MSME financing is the Musyarakah contract.…”
Section: Introductionsupporting
confidence: 79%
“…Research related to the role of Islamic banks in the strengthening of SMEs also have a lot to do, citing the results of the analysis of the Ministry of Commerce that SMEs have a very important role in the economic growth of a country. Saleh & Hadiyat (2016), it is in line with the results of the study (Rini, 2017), (Prayogi & Siregar, 2017), (Kara, 2014), (Cheng & Degryse, 2010) in his research revealed that poor communities in border areas are able to improve their standard of living by empowering MSMEs, but are still constrained by the level of education in managing MSMEs. (Trimulato, 2017), (Aurora Lubis, 2016), (Darwanto, 2013) in his research identified that the most suitable Islamic banking financing for MSME financing is the Musyarakah contract.…”
Section: Introductionsupporting
confidence: 79%
“…This number is still insufficient. The level of education is one aspect that determines the adoption of digital technology for MSEs (Saleh & Hidayat, 2016;Statistics Indonesia, 2019).…”
Section: The Use Of the Internet (Digital Technology)mentioning
confidence: 99%
“…Oleh karena itu UMKM cukup besar berperan dalam pertumbuhan perekonomian khususnya di Indonesia. Walaupun demikian pengembangan UMKM masih relatif lambat, terutama dalam hal peningkatan produksi dan daya saing usaha (Saleh & Hadiyat, 2016). Septiani, Chandraderia, Arini, Pratomo, Peran Usaha Maju… https://doi.org/10.35760/eb.2020.v25i2.2500…”
Section: Hasil Dan Pembahasanunclassified